Critical indirect effects of climate change on sub‐Antarctic ecosystem functioning. Issue 9 (31st July 2013) - Louise Allan, E.; William Froneman, P.; Durgadoo, Jonathan V.; McQuaid, Christopher D.; Ansorge, Isabelle J.; Richoux, Nicole B.
Abstract: Sub‐Antarctic islands represent critical breeding habitats for land‐based top predators that dominate Southern Ocean food webs. Reproduction and molting incur high energetic demands that are sustained at the sub‐Antarctic Prince Edward Islands (PEIs) by both inshore (phytoplankton blooms; "island mass effect"; autochthonous) and offshore (allochthonous) productivity. As the relative contributions of these sustenance pathways are, in turn, affected by oceanographic conditions around the PEIs, we address the consequences of climatically driven changes in the physical environment on this island ecosystem. We show that there has been a measurable long‐term shift in the carbon isotope signatures of the benthos inhabiting the shallow shelf region of the PEIs, most likely reflecting a long‐term decline in enhanced phytoplankton productivity at the islands in response to a climate‐driven shift in the position of the sub‐Antarctic Front. Our results indicate that regional climate change has affected the balance between allochthonous and autochthonous productivity at the PEIs. Over the last three decades, inshore‐feeding top predators at the islands have shown a marked decrease in their population sizes. Conversely, population sizes of offshore‐feeding predators that forage over great distances from the islands have remained stable or increased, with one exception. Population decline of predators that rely heavily on organisms inhabiting the inshore region strongly suggest changes in prey availability, which are likely driven by factors such as fisheries impacts on some prey populations and shifts in competitive interactions among predators. In addition to these local factors, our analysis indicates that changes in prey availability may also result indirectly through regional climate change effects on the islands' marine ecosystem. Most importantly, our results indicate that a fundamental shift in the balance between allochthonous and autochthonous trophic pathways within this island ecosystem may be detected throughout the food web, demonstrating that the most powerful effects of climate change on marine systems may be indirect. Abstract : We have found a long‐term southward migration of the sub‐Antarctic Front is coupled with a long‐term depletion of δ 13 C signatures in the inshore benthos, likely reflecting a long‐term decline in phytoplankton productivity at the sub‐Antarctic Prince Edward Islands. Furthermore, a decline in the abundances of inshore‐feeding top predators at these islands indicates changes in prey availability, which may have resulted indirectly through the effects of regional climate change on the marine ecosystem at these islands.